Synthesis and characterization of pentaerythritol derived glycoconjugates as supramolecular gelators. Issue 24 (3rd June 2019) - Chen, Anji; Wang, Dan; Bietsch, Jonathan; Wang, Guijun
Abstract : Three series of glycoclusters were synthesized and studied and we found that covalently linking three or four monomeric glycosyl triazoles led to effective supramolecular gelation. Abstract : Carbohydrate based self-assembling supramolecular systems are important classes of new materials with many potential applications. In this study, a series of twelve glycoconjugates were synthesized and characterized in order to obtain effective supramolecular gelators. These glycoconjugates are mono-, di-, tri-, and tetra-functionalized pentaerythritol derivatives synthesized by using copper(i ) catalyzed azide alkyne cycloaddition reactions (CuAACs). The properties of these twelve compounds gave insight into the rational design of covalently linking multiple units of sugars. We found that the trivalent and tetravalent glycoclusters were effective molecular gelators, but the monovalent and divalent derivatives were typically not able to form gels in the tested solvents. The gels were characterized using rheology, optical microscopy, and atomic force microscopy. The tris-triazole derivative21 was discovered to be a suitable gelator for the encapsulation of naproxen, vitamin B2, and vitamin B12 . The strategy of covalently linking three or four small molecules to form trimeric or tetrameric branched compounds is a valid approach in designing useful self-assembling materials. The glycocluster based organogels and hydrogels obtained in this study have potential applications in biomedical research and as advanced functional materials.